2007
DOI: 10.1002/jbm.a.31687
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Sr doses on the in vitro biocompatibility and in vivo degradability of single‐phase Sr‐incorporated HAP cement

Abstract: In previous studies, we developed a new type of Sr-incorporated hydroxyapatite cement (Sr-HAC), which was shown to have many excellent physiochemical properties, by an ionic cement route (Guo et al., Biomaterials 2005;26:4073-4083). As a further study, the main aims of this article were to examine the Sr-HAC's in vitro biocompatibility, including acute toxicity, hemolytic reaction, pyrogen reaction, and cytoxicity, to evaluate its in vivo degradability during intramuscular and femur implantation, and also to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 37 publications
4
25
1
Order By: Relevance
“…These results contradict the findings of Dagang et al, 32 who evaluated a strontium-containing HA cement and showed that it had better osteoconductivity, biocompatibility and biodegradability than HA-only cement. Biocompatibility testing performed by these authors revealed that the 5% strontium-containing …”
contrasting
confidence: 94%
“…These results contradict the findings of Dagang et al, 32 who evaluated a strontium-containing HA cement and showed that it had better osteoconductivity, biocompatibility and biodegradability than HA-only cement. Biocompatibility testing performed by these authors revealed that the 5% strontium-containing …”
contrasting
confidence: 94%
“…36,37 However, two of the three authors who specifically compared different Sr percentages found an increased overall response with higher concentrations, 24,34 confirming previous in vitro reports. 52 The other author reported similar results between E and C. 28 All three authors agree that the optimum dose of Sr is yet to be discovered, since it can impact both the bone response and material properties.…”
Section: Discussionsupporting
confidence: 82%
“…52 The other author reported similar results between E and C. 28 All three authors agree that the optimum dose of Sr is yet to be discovered, since it can impact both the bone response and material properties. 24,28,34 …”
Section: Discussionmentioning
confidence: 99%
“…Although these results suggest that the Sr leaching behavior was related to the pH, we are unable to provide a plot of the solubility of strontium hydroxide with respect to the pH. Many literature reports have described the cytotoxicity of Sr and its compounds [22][23][24][25]. Keller reported that 89 Sr could suppress the spontaneous cytotoxicity in mouse tissues [22].…”
Section: Literature Review Of the Behavior Ecotoxicity Of Sr In Solidmentioning
confidence: 83%
“…Keller reported that 89 Sr could suppress the spontaneous cytotoxicity in mouse tissues [22]. In recent years, Sr-incorporated hydroxyapatite cement [23] and calcium phosphate cement [24] have been developed as new biomedical materials, which exhibit good compatibility and low cytotoxicity, for use in human bones. An in vitro test revealed that strontium ranelate is non-toxic toward human periodontal ligament fibroblasts [25].…”
Section: Literature Review Of the Behavior Ecotoxicity Of Sr In Solidmentioning
confidence: 99%